PENGGUNAAN MEDIA SOSIAL TWITTER DALAM PEMBENTUKAN DIMENSI EKUITAS MEREK L-MEN - Widya Darmawati; Saepudin . (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2015)
Nowadays, social media is used for branding and it is not only being trend, but a requirement to keep in touch with the audiences. It is caused by the number of social media user which getting increase day per day. Social media could be an alternative media for branding and making stronger brand equity. L-Men also uses Twitter to inform and interact with the audiences. This research discuss the framework of L - Men while using Twitter and what kind of brand equity that constructed on its account. This research used qualitative method. It found that L-Men has its own goal, objective, strategies, and tactics on using Twitter for branding. Furthermore, brand awareness dimension has been constructed on using its Twitter. But, the other dimensions –such as brand association, perceived quality, and brand loyality- have not been constructed as well as brand awareness dimension